LAN NETWORK MANAGEMENT SYSTEM DESIGN IN PT. ABC - Mellviana Chandra; Drs. Lingga Hermanto, MM (Jurnal Sistem Komputer, 1998)
In all cases, the process of choosing what type of system and network to the appropriate network operating system relies heavily on an understanding of running a business firm (in terms of managing data and information into something meaningful). Hence thing to note is studied process data and information flow within an existing business in a way to analyze and evaluate as precisely as possible. Emphasized here that the selected network must support and reflect the ways data / information flow or process in the conduct of company business. Reviewing and analyzing the data stream back to processed into useful information, and efforts to improve management processes, and visualize network support for the improvement company.